The Relationship Between Nutritional Status and Intellectual Intelligence in School-Age Children at State Islamic Elementary School (MIN) 11, West Aceh - Hayati, Mir Atil; Anwar, Sufyan; Iskandar, Wardah; Mulyani, Itza (Journal of Nutrition Science, 2025)
Nutritional status plays an important role in children's growth and development, including cognitive function. However, intellectual intelligence in school-age children is influenced by various biological and environmental factors. This study aims to examine the relationship between nutritional status and intellectual intelligence in school-age children at Madrasah Ibtidaiyah Negeri (MIN) 11 Aceh Barat. This study uses an analytical design with a cross-sectional approach. The study population consisted of all sixth-grade students at MIN 11 Aceh Barat, with a total of 104 respondents selected using total sampling technique. Nutritional status was assessed using the Body Mass Index for Age (BMI/A) indicator, while intellectual intelligence was measured using the Culture Fair Intelligence Test (CFIT) Scale 2A. The results showed that most respondents had normal nutritional status (65.4%) and moderate (60.6%) and high intellectual intelligence ((27.9%). The results of Chi Square Test showed that there was no significant relationship between nutritional status and intellectual intelligence in school-age children (p = 0.715). Therefore, efforts to improve children's intellectual intelligence need to be carried out comprehensively through a multidimensional approach integrating aspects of nutrition, education, and the environment.